Can the Culture of Honor Lead to Inefficient Conventions? : Experimental Evidence from India - Brooks, Benjamin (World Bank, Washington, DC, 2016)
Experiments in the United States have found that pairs of individuals are generally able to form socially efficient conventions in coordination games of common interest in a remarkably short time. This paper shows that this ability is not universal. The paper reports the results of a field experiment in India in which pairs of men from high and low castes repeatedly played a coordination game of common interest. Low-caste pairs overwhelmingly coordinated on the efficient equilibrium, consistent with earlier findings. In contrast, high-caste pairs coordinated on the efficient equilibrium at a much lower rate, with only 47 percent in efficient coordination in the final period of the experiment. The study traces the divergence in outcomes to how an individual responds to the low payoff he obtains when he attempts efficient coordination but his partner does not. After this event, high-caste men are significantly less likely than low-caste men to continue trying for efficiency. The limited ability to form the efficient convention can be explained by the framing effect of the culture of honor among high-caste men, which may lead them to interpret this event as a challenge to their honor, which triggers a retaliatory response.